Reconstruction of Macroscopic Maxwell Equations A Single Susceptibility Theory - Cho, Kikuo (Springer Tracts in Modern Physics,, 2018)
This book discusses the electromagnetic response function of matter, providing a logically more complete form of macroscopic Maxwell equations than the conventional literature. It shows that various problems inherent to the conventional macroscopic Maxwell equations are solved by the first-principles derivation presented. Applying long wavelength approximation to microscopic nonlocal response theory results in only one susceptibility tensor covering all the electric, magnetic and chiral polarizations, and the book provides its quantum mechanical expression in terms of the transition energies of matter and the lower moments of corresponding current density matrix elements. The conventional theory in terms of epsilon and mu is recovered in the absence of chirality under the condition that magnetic susceptibility is defined with respect to not H, but to B. This new edition includes discussions supporting the basis of the present electromagnetic response theory in a weakly relativistic regime, showing the gauge invariance of many-body Schroedinger equation with explicit Coulomb potential, the relationship between this theory and the emergent electromagnetism, and the choice of appropriate forms of single susceptibility theory and chiral constitutive equations.